CUSTOMER AWARENESS TOWARDS MOBILE BANKING IN RURAL AREAS OF AGASTEESWARM TALUK (International Journal of Food and Nutritional Sciences, 2022)
Mobile Banking plays fundamental roles within the ongoing scenario, based on the up gradation of the generation client of the banks have begun the usage of the banking services via the use of smart phones. Present days most of the normal people started using smart phones and cell phones have end up the primary need of every one that helps the customers to make various varieties of activities. The Activities which are carried out with the assist of Mobile Banking are on line switch of money, Ticket reservation, and transfer of price range, and so forth, Customer awareness towards mobile banking usage in rural areas. Government of India has been enforcing many schemes Digital India programme and so on, with the vision transformation into the society of digitally empowered. (Virtual) with the brand-new development of generation, Government has expanded its platform from electronic governance to Mobile governance that's turning into the favourite mode with the aid of the citizens. Mobile phones have taken a vital space as a communique tool in our existence. Banks additionally have changed the approach of banking offerings to their benefactor. Now benefactor can perform their banking transactions from everywhere each time with the assist of m-banking. the pilot takes a look at turned into done to locate the awareness about the Mobile banking software among the rural citizens from Agasteeswarm TalukFor that, the researcher collected 75samples from the respondents and percentage, Garret ranking method and t- test used for this study.